Respuesta :
y - 1 / 6 = ( 3 / 5 ) ( x - 0 ) ;
y - 1 / 6 = ( 3x / 5 ) ;
( 30 y ) / 30 - 5 / 30 = ( 18x ) / 30 ;
30y - 5 = 18x ;
30y - 18x - 5 = 0 .
y - 1 / 6 = ( 3x / 5 ) ;
( 30 y ) / 30 - 5 / 30 = ( 18x ) / 30 ;
30y - 5 = 18x ;
30y - 18x - 5 = 0 .
y - y₁ = m(x - x₁)
y - ¹/₆ = ³/₅(x - 0)
y - ¹/₆ = ³/₅(x) - ³/₅(0)
y - ¹/₆ = ³/₅x - 0
+ ¹/₆ + ¹/₆
y = ³/₅x + ¹/₆
y = ³/₅(0) + ¹/₆
y = 0 + ¹/₆
y = ¹/₆
y - ¹/₆ = ³/₅(x - 0)
y - ¹/₆ = ³/₅(x) - ³/₅(0)
y - ¹/₆ = ³/₅x - 0
+ ¹/₆ + ¹/₆
y = ³/₅x + ¹/₆
y = ³/₅(0) + ¹/₆
y = 0 + ¹/₆
y = ¹/₆